Kepentingan Indonesia dalam Kerja Sama Bilateral dengan Jepang (IJEPA) dalam Bidang Industri Otomotif - Octaviania Mediswastya Hidayat; M. Syaprin Zahidi (Indonesian Journal of Global Discourse, 2023)
IJEPA is a bilateral cooperation in the economic field between Indonesia and Japan. The first bilateral free trade agreement was conducted by Indonesia, especially in the automotive sector. This research aims to understand the national interest of bilateral cooperation between Indonesia and Japan in IJEPA related to the trade of the Japanese automotive industry in Indonesia. Furthermore, this article also uses the concepts of bilateral cooperation and national interests. Besides, this research is descriptive-qualitative research that uses the method of library research to collect data. The results showed that Indonesia's interest in IJEPA regarding the Japanese automotive industry trade in Indonesia is divided into three namely: (1) short-term interest with self-preservation, which supports the welfare of Indonesian people, (2) medium-term interests, which consist of improving the economy in order to increase market access for goods, increase Japanese investment in Indonesia, and making Indonesia the center of the global automotive industry, (3) long-term interest, namely the new world order, where the cooperation carried out in the automotive industry trade will create a positive contribution to both countries.